An investigation on Aluminothermic reduction of MoO3 in domestic microwave oven - Sheybani, Kazem; Paydar, Mohammad Hossein; Shariat, Mohammad Hossein; Setoodeh, Nader (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
In the present study, feasibility of aluminothermic reduction of molybdenum oxide by microwave oven was studied. Furthermore, the effect of compaction pressure, the amount of used Al and CaO, as flux on aluminothermic reduction of molybdenum oxide were investigated. Thermodynamic analysis of the corresponding reaction indicated that, the reduction of MoO3 by Al is thermodynamically feasible at room temperature. XRD patterns and thermodynamic investigation of reaction products indicated that aluminothermic reduction of molybdenum oxide progressed through the formation of intermediate phases such as Al2 (MoO4)3 and MoO2, where the final products were elemental Mo and Al2O3. Results revealed that by increasing the compaction pressure of the pellet, undesired phases of molybdenum dioxide (MoO2) and aluminum molybdate Al2(MoO4)3 can be detected among the final products. By increasing the amount of Al more than stoichiometric ratio, the intermediate phases such as MoO2 is produced. The results indicated that by adding CaO to the MoO3-Al system, the unwanted molybdenum dioxide (MoO2) and aluminum molybdate (Al2 (MoO4)3) compounds were successfully reduced to Mo. In the present work, metallic molybdenum could easily and successfully be separated from Al2O3 slag, as the side product of the reaction, in molten phase, based on the difference in their densities.